2011
DOI: 10.1111/j.1750-3841.2010.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Storage on Dark Chocolate: Texture and Polymorphic Changes

Abstract: Chocolate storage is critical to final product quality. Inadequate storage, especially with temperature fluctuations, may lead to rearrangement of triglycerides that make up the bulk of the chocolate matrix; this rearrangement may lead to fat bloom. Bloom is the main cause of quality loss in the chocolate industry. The effect of storage conditions leading to bloom formation on texture and flavor attributes by human and instrumental measures has yet to be reported. Therefore, the impact of storage conditions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Thus, high‐temperature storage would cause chocolate samples to be lighter in color (Nightingale et al . ). Low water activity ( A w ) ranging from 0.45 to 0.70 was observed in both chocolates (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, high‐temperature storage would cause chocolate samples to be lighter in color (Nightingale et al . ). Low water activity ( A w ) ranging from 0.45 to 0.70 was observed in both chocolates (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…During storage, various physicochemical processes occur in chocolate products, that is, hydrolysis, oxidation, lipid migration, water migration, and ethanol migration as well as transformation in sugars-sugar bloom and sucrose inversion. 16 Water migration typically occurs in the products with a difference in the water activity of the filling and that of the external coating. 17 The consequences of migration may involve product damage, expressed as cracking of the external portion; drying out of the internal portion; or appearance of mold.…”
Section: Discussionmentioning
confidence: 99%
“…adhesiveness (P: 0.000108 < 0.05), cohesiveness (P: 0.018688 < 0.05) and springiness (P: 0.018562 < 0.05) on account of temperature fluctuations under ambient conditions were. Nightingale et al (2011) reported the textural changes in dark chocolate stored at ambient (storage room) and temperature fluctuations. The percent change in hardness, cohesiveness and springiness after 8 weeks of storage was less than 10 per cent for temperature fluctuations environment.…”
Section: Rajmalaimentioning
confidence: 99%